2016
DOI: 10.1016/j.jmmm.2015.08.071
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic domain-wall velocity enhancement induced by a transverse magnetic field

Abstract: Spin dynamics of field-driven domain walls (DWs) guided by Permalloy nanowires are studied by high-speed magneto-optic polarimetry and numerical simulations. DW velocities and spin configurations are determined as functions of longitudinal drive field, transverse bias field, and nanowire width. Nanowires having cross-sectional dimensions large enough to support vortex wall structures exhibit regions of drive-field strength (at zero bias field) that have enhanced DW velocity resulting from coupled vortex struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Recently we have reported that stress annealing of Fe-rich microwires results in induced transverse magnetic anisotropy that can be beneficial for further DW velocity improvement 36,37,43,44 . Therefore, we performed stress annealing of the Fe 75 B 9 Si 12 C 4 microwire.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we have reported that stress annealing of Fe-rich microwires results in induced transverse magnetic anisotropy that can be beneficial for further DW velocity improvement 36,37,43,44 . Therefore, we performed stress annealing of the Fe 75 B 9 Si 12 C 4 microwire.…”
Section: Resultsmentioning
confidence: 99%
“…We can assume that this outer domain shell with transverse magnetic anisotropy affects the travelling DW in a similar way as application of transversal bias magnetic field allowing enhancement the DW velocity 36,37,42,43 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stretching mode is not one of the compact DW configurations and is a special type of mode that is affected dramatically by an applied magnetic field perpendicular to the nanowire axis and the thickness axis. This mode has been described in detail in prior publications [28], and will be briefly discussed in Section VI that outlines experimental evidence for the various modes described above. Mobility curves exhibit systematic temperature dependent shifts that are similar to static magnetic bias-field shifts reported in prior publications [28] and which are consistent with shifts of measured mobility curves described later.…”
Section: Domain Wall Dynamicsmentioning
confidence: 97%
“…The average forward motion of the core is slowed by the oscillatory displacement along the wire as H increases which accounts for the negative differential mobility. This region of complex oscillatory motion has been explored experimentally [8,10] and theoretically by analytical models [10] and by prior numerical simulations [10,22,28].…”
Section: Domain Wall Dynamicsmentioning
confidence: 99%